What is wrong with Europe's shattered Single Market? Lessons from policy fragmentation and misdirected approaches to EU competition policy - Matthias Bauer (European Centre for International Political Economy (ECIPE), 2023)
What is wrong with Europe's Single Market? The brief answer to that question is that it does not really exist - it is unsingle. The Single Market is in many ways a political illusion. It exists only nominally. Any company doing business in Europe faces significant barriers to cross-border exchanges within the EU, and it is these barriers that hamper companies' ability to scale and compete internationally on the back of innovation and economic integration. We outline that Brussels and national governments need to beat the drum for eliminating policy fragmentation in Europe's internal market and at the same time change course in competition policy to sufficiently support investments in innovation, business growth, and the adoption of advanced technologies across industries.
Keywords: 330; EU internal market; trade barriers; EU states; EU-Binnenmarkt; Handelshemmnisse; EU-Staaten